2016
DOI: 10.5937/sjm11-8480
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between leadership communication style, personality trait and organizational productivity

Abstract: Leadership position stands as one of the subtle positions in today's corporate organizations. It is a position that must be assigned or emerged based on merits. Leadership based on political calculations or nepotisms will not drive organizational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 9 publications
2
26
0
3
Order By: Relevance
“…Thus, we can draw a conclusion that through the humanistic approach of the principal, the image of the school has changed meaning into a forum for empowering student characters. Schools become a conducive environment to the practice of learning to love, independence, discipline, ethical thinking, uphold the moral values of humanity, promote loyalty, responsibility, and care for others (Solaja, Idowu, & James, 2016).…”
Section: Forms Of Activities For Character Education Strengthening Anmentioning
confidence: 99%
“…Thus, we can draw a conclusion that through the humanistic approach of the principal, the image of the school has changed meaning into a forum for empowering student characters. Schools become a conducive environment to the practice of learning to love, independence, discipline, ethical thinking, uphold the moral values of humanity, promote loyalty, responsibility, and care for others (Solaja, Idowu, & James, 2016).…”
Section: Forms Of Activities For Character Education Strengthening Anmentioning
confidence: 99%
“…Thomas and Thomas (2011:530) argue that leadership uses critical and constructive debates, communication, open examination and 'thinking outside the box' in order for the academia to be successful. A study conducted on 112 staff at the University of Lagos in Nigeria by Solaja, Idowu and James (2016) suggested that university leaders should mainstream all employees in the decision-making processes, which will increase creativity and innovation amongst them. Coates et al (2010:381) mention major features of a conducive university arena, which include administrative efficiency, autonomy and the involvement of employees in the decisionmaking structures.…”
Section: Leadership and Decision-making In Universitiesmentioning
confidence: 99%
“…No matter how intelligent or confident a person is, if they lack effective communication skills it is highly unlikely that they will be successful as a leader. A study by Solaja et al examined the relationship between leadership communication style, personality traits, and organizational productivity [29]. They surveyed 112 academic staff to determine their perceptions.…”
Section: Leadership Communicationmentioning
confidence: 99%
“…They surveyed 112 academic staff to determine their perceptions. The results of the study revealed that a connection between leadership communication style and personality traits does exist, that leadership communication style determines organizational productivity, and that personality traits and communication styles together have an effect on organizational productivity [29]. Employee motivation and satisfaction have also been shown to be dependent on effective communication [30].…”
Section: Leadership Communicationmentioning
confidence: 99%